Anti-IgLON5 disease complicated with rectal adenocarcinoma: a case report - Yi Li; Lili Zhang; Yuzhong Wang (BMC Neurology, 2023)
Abstract Background Anti-IgLON5 disease is a rare chronic autoimmune-mediated tauopathy, featured by the sleep disturbance. Several studies have described its clinical characteristics, however, the simultaneous occurrence of anti-IgLON5 disease and rectal cancer has not been reported. We described an unusual entity of anti-IgLON5 disease complicated with rectal cancer. Case presentation A 76-year-old man initially presented with slurred speech and limb tremors, followed by epileptic-like seizures, lethargy, and sleep apnea. IgG anti-IgLON5 antibodies were positive in both serum and cerebrospinal fluid. The patient responded well to the treatment of plasma exchange and a pulse and gradual reduction of steroids therapy. When the oral steroids started, mycophenolate mofetil was added. Two months later, the patient had bloody stools and pathological-confirmed moderately differentiated adenocarcinoma of the rectum. Conclusions Whereas sleep disturbance is the most common feature in patients with anti-IgLON5 disease, our case presented with slurred speech and limb tremors. Anti-IgLON5 disease complicated with rectal cancer is very rare. Tumor screening should be considered in patients with anti-IgLON5 disease to investigate the association between tumor and this disease.